Pengaruh Kampanye Digital Pemerintah terhadap Kesadaran Masyarakat Mengenai Kebijakan Luar Negeri Indonesia - Mohammad Firdan Walang; Haenry Adam; Nia Raihana S; Naufal Abdillah P; Alvian Ariadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The use of digital campaigns by the government has become an increasingly important tool in explaining foreign policy to the public, especially on complex and sensitive issues such as Indonesia's humanitarian diplomacy towards Palestine. However, the extent to which these digital campaigns influence public awareness has rarely been tested quantitatively. This study aims to analyze the influence of Government Digital Campaigns (KDP) on Public Awareness of Indonesian Foreign Policy (KMKLN) with a focus on the issue of Indonesian aid to Palestine. The study uses a quantitative approach through an online survey of 30 respondents who are active social media users. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability, then analyzed using simple linear regression. The results show that the government's digital campaign has a positive and significant effect on public awareness (β = 0.541; t = 5.577; p < 0.001). The coefficient of determination (R² = 0.526) indicates that 52.6% of the variation in public awareness can be explained by the government's digital campaign. These findings support the agenda-setting theory and media exposure theory, which state that the intensity and quality of digital message exposure can increase public knowledge and understanding. This study concludes that government digital campaigns are a strategic instrument in increasing public awareness of foreign policy, although it is necessary to strengthen the quality of content and expand the audience reach in order to optimize its impact.